Transparency in public management and its impact on the right of access to information (Gestionar: revista de empresa y gobierno, 2021)
The study determined transparency and its impact on access to public information in the Puno region. Compliance with transparency in general management was diagnosed, the conditions of access to public information were described since access to public information is essential as a tool to fight corruption. The descriptive method was applied through a meticulous analysis that allowed to determine the transparency; documentary analysis and direct observation were also used. The results indicated that 69% of the heads of the investigated entities did comply with the appointment of the official responsible for updating the transparency portal and responsible for access to public information. Furthermore, 62% complied with the publication of general data, being the responsibility of the responsible official to update this information regarding the publication of management instruments. Therefore, it can be said that the results are optimal; in this way, citizens can have access to this information.
Keywords: Access to information; public management; transparency